The impact of hikmah (Wisdom) pedagogy on 21st century skills of selected primary and secondary school students in Gombak district Selangor Malaysia - Wan Yusoff, Wan Mazwati; Hashim, Rosnani; Hussien, Suhailah; Khalid, Madihah; Kamalludeen, Rosemaliza (Canadian Center of Science and Education, 2018)
In this paper the impact of Hikmah Pedagogy (HP) on critical, creative, caring and collaborative thinking and communication skills of students in primary and secondary schools through the subjects of Malay (also known as Bahasa Malaysia) and English languages were investigated. The participating teachers were trained by experts from the Center for Teaching Thinking, International Islamic University Malaysia (IIUM) and they were observed and supervised to ensure HP was implemented correctly. This study employed the case study method to collect both quantitative and qualitative data. The quantitative data were collected before and after the intervention of the HP using the Cognitive Behavior Checklist. Mid-semester and final examination results were used to gauge improvement in English and Bahasa Malaysia. These data were analysed using descriptive and inferential statistics. The qualitative data were collected through interviewing teachers individually at the beginning and focus group discussion (FGD) at the end of study. The data were analysed qualitatively to identify the emerging themes. The findings show that when students were given opportunity to ask questions based on the given stimulus materials and to voice out their opinions in the dialogic approach of HP, they demonstrated the ability to reason well; think about their own thinking; to think caringly and collaboratively. Students showed improvement in their communication skills in both languages which were indicated by the increase in their examination results, particularly in writing and oral skills.